Visual grammar analysis of tourism promotion on Instagram: Representational and ideational meanings - Aisyiyah, Siti (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Tourism is one of the prospective sectors to increase the Indonesian economic level. It is crucial to develop effective promotion media for tourist destinations in Indonesia. One of the recent potential media is Instagram. This paper aims to investigate the ideational and representational meaning of visual and verbal modes in promoting Taman Nasional Komodo Labuan Bajo, focused on @btn_komodo as an official Instagram account of Balai Taman Nasional Komodo. The destination is one of the 5 super priority destinations in Indonesia. By applying the Visual Grammar framework (Kress & Leeuwen, 2006), this study views how the visual and verbal modes construe the meaning for the purpose of tourism promotion on Instagram. The data was captured from Instagram posts in the form of visual texts (photos) and verbal texts (captions). The posts are predominantly communicated through the visual text, then completed, clarified, and confirmed by the accompanying verbal text. Multimodal discourse analysis of the Instagram posts shows that both visual and verbal texts contribute to the values of promotion. The result implies that future research should include more complete material on semiotic resources and implement more comprehensive analysis related to multimodal discourse.